A prospective study on the relationship between COVID-19 disease progress and cardiovascular damage - Kaya, Bedri Caner; Çekici, Yusuf; Kaya, Berna; Celik, Ahmet; Demir, Hüseyin Avni; Yılmaz, Nurdan (Journal of Surgery and Medicine, 2021)
Background/Aim: Covid-19 is a new coronavirus disease with high mortality that has reached all parts of the world. This study aimed to prospectively compare individual characteristics, echocardiographic findings, and laboratory findings in patients with Covid-19 according to the need for intensive care unit (ICU) admission and mortality. Methods: In this single-center prospective cohort study, patients hospitalized with the diagnosis of Covid-19 between June and November 2020 were examined in terms of echocardiographic and laboratory results. Early in-hospital findings that might affect mortality, cardiac injury and thrombotic complications were evaluated and compared. Results: A total of 214 patients who were hospitalized due to Covid-19 were included in our study, 80 (37.3%) of which needed hospitalization in the ICU and 134 (62.6%) of which did not. The mean ages of patients treated in the ICU unit and the ward were 69.5 (57.5-80.5) years and 40 (29-58) years, respectively (P<0.001). Among patients hospitalized in the ICU, mean Troponin T on Day 1 (27.12 ng / L, range: 10.48-70.51, P<0.001), mean Troponin T on Day 3 (31.5ng / L, range: 10.24 - 114.5, P<0.001) and mean D-dimer (2.84ng / L, range: 1.1-8.22, P<0.001) levels of those who died were significantly higher compared to survivors. These parameters were important markers of mortality along with right ventricular end-diastolic diameter (RVDD) (3.3 cm (2.8-3.7) P<001). Conclusion: While cardiac damage and high D-dimer values suggest the possibility of pulmonary microembolism in those who need ICU hospitalization, the relationship between RVDD and mortality supports the possibility of pulmonary embolism.